Case-matched comparison of long-term results of non-heart beating and heart-beating donor renal transplants - Barlow, A. D.; Metcalfe, M. S.; Johari, Y.; Elwell, R.; Veitch, P. S.; Nicholson, M. L. (British journal of surgery, 2009)
Background: Function and survival of non‐heart‐beating donor (NHBD) renal transplants have been shown to be comparable to those from heart‐beating donors (HBDs) up to 10 years after transplantation. However, there are few data on outcome after 10 years, particularly from uncontrolled NHBD donors. Methods: All NHBD renal transplants (predominantly uncontrolled) performed between April 1992 and January 2002 were retrospectively matched with HBD renal transplants performed over the same period. Results: Some 112 NHBD renal transplants were compared with 164 HBD renal transplants. Delayed graft function was significantly higher in the NHBD group (83·9 versus 22·0 per cent respectively; P < 0·001). Primary non‐function rates were similar (5·4 versus 1·8 per cent respectively; P = 0·164). Overall serum creatinine was significantly higher in NHBDs (P < 0·001). Median graft and patient survival was 126 months for NHBD and 159 months for HBD kidneys. Death‐censored graft survival at 1, 5, 10 and 15 years was respectively 91·8, 77·5, 61·0 and 44·2 per cent for NHBD, and 91·1, 86·3, 71·7 and 58·5 per cent for HBD kidneys (P = 0.108). Conclusion: Despite increased delayed graft function rates and serum creatinine levels, the long‐term survival of NHBD renal transplants was similar to those from HBDs. However, there was a trend to poorer function and survival from 10 years after transplant. Copyright © 2009 British Journal of Surgery Society Ltd. Published by John Wiley & Sons, Ltd. Comparable survival